The digital echo atlas : a multimedia reference - Clements, Stephen David, Jr., 1940- (Philadelphia : Wolters Kluwer, 2019)
'The Digital Echo Atlas establishes a robust, extensive, imaging resource for the cardiology list by providing a digital library of hundreds of topics with accompanying echo clips, and for some topics, MRI, EKGs, and CT scans covering the entire heart structure and gamut of cardiovascular abnormalities. Text is minimal, with the emphasis placed on the images, clips, and figures. The digital focus of this atlas brings the echo clips to life, allowing the viewer to see them as they would appear in the lab and to view the material conveniently from their mobile device. Many of the topics also include cases, which allow the user to gain a better understanding of when they might encounter a particular condition and how it should be approached. Dr. Clements continues to add cases to his collection and will provide additional cases throughout the life of the title, ensuring the content remains updated. This resource can be used as a learning and reference tool by cardiology fellows, junior practitioners, NPs/PAs, and residents, or as a mobile teaching tool on rounds or in the classroom'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Echocardiography; Atlas